Design and development of mechanical linkage steering system for go-kart - Abdul Razak, Auni Azira; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project focuses on the design and development of a Go-Kart Direct Mechanical Linkage Steering System. Three initial design concepts were sketched, and the final design was modeled using SolidWorks software. After modifications, the system was fabricated over a 13-week period. The fabrication process included cutting, turning, grinding, welding, and assembly, ensuring the system's structural integrity and functionality. The fabricated steering system was tested at its maximum steering angle to evaluate performance, demonstrating reliability and precision in maneuvering the go-kart. The system offers simplicity, cost effectiveness, and a direct mechanical connection, providing quick and responsive steering. However, it requires manual effort and regular maintenance. By analyzing the system’s design, fabrication, and performance, this study contributes to optimizing mechanical linkage steering for go-karts, enhancing safety, durability, and efficiency. The findings provide insights into improving future steering systems for recreational and competitive applications.